Information resources, information skills and education : an exploratory study of information literacy education in community junior secondary schools in the North-East district of Botswana and the role of teacher-librarians and school libraries - Mugabe, Mover M (Library and Information Studies Centre (LISC), 2015)
Bibliography: leaves 155-160.